Application of Shenque acupoint (RN8) application with Xiere Tongbian patch to promote the defecation after anorectal surgery (泄热通便贴脐敷促进肛肠疾病术后排便的效果观察) - LIU Lijuan (刘丽娟); HAO Li (郝丽); XU Yunxia (许云霞); XU Shanying (许山鹰) (中西医结合护理)
Objective To investigate the effect of Shenque acupoint (RN8) application with Xiere Tongbian patch to promote the defecation after anorectal surgery. Methods Totally 100 patients undergoing colorectal surgery were randomly divided into 2 groups: 50 patients in the control group received routine wound care, 50 patients in the intervention group received treatment with Chinese herbal medicine Xiere Tongbian patch on Shenque acupoint(RN8) in addition to the routine wound care. Clinical efficacy and patient comfort level were measured and compared between two groups. Results The marked effective rate was 70. 00%(35/50)in the intervention group, which was higher than 22. 00%(11/50), with a significant difference (P＜0. 01). The rate of discomfort was 16. 00%(8/50)in the intervention group, which was lower than 42. 00%(21/50), with a significant difference (P＜0. 01). Conclusion In addition to routine wound care for constipation after anorectal surgery, using Chinese herbal medicine patch on Shenque acupoint (RN8) is potentially effective in patient’s constipation management, and it is well accepted by patients. (目的 观察泄热通便贴脐敷促进肛肠病局部手术后排便的效果。方法 选取肛肠病局部手术后患者100例为研究对象, 随机分为干预组和对照组, 各50例。对照组术后给予常规换药和护理, 干预组在对照组基础上增加中药泄热通便贴脐敷干预。评价临床干预效果和患者不适感。结果 干预组显效率为70. 00%(35/50), 高于对照组的22. 00%(11/50), 差异有统计学意义(P＜0. 01); 干预组不适感率为16. 00%(8/50), 低于对照组的 42. 00%(21/50), 差异有统计学意义(P＜0. 01)。结论 泄热通便贴脐敷能有效促进肛肠疾病局部手术后排便, 且患者易于接受, 值得借鉴。)